2012
DOI: 10.20452/pamw.1351
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury after abdominal aortic aneurysm surgery: detailed assessment of early effects using novel markers

Abstract: INTROduCTION One of the most severe complications of repair surgery for abdominal aortic aneurysms (AAA) is acute kidney injury (AKI). Even small rises in serum creatinine after surgery are associated with increased mortality. ObjECTIvEs The aim of the study was to assess the dynamics of AKI after elective AAA surgery using novel markers. PATIENTs ANd mEThOds The study group consisted of 14 patients with AAA. We measured serum neutrophil gelatinase-associated lipocalin (NGAL) before, during (including intra-ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…The systemic inflammation highlighted in AAD patients was also associated with an imbalance of pro-coagulant and vasoconstrictor factors including D-dimer, CFIII, s-Psel and EN-1, which are deregulated compared to controls, although we found no real differences between type A and B patients. Our findings with ICAM-1 agree with previous studies [28, 29], which reported that during the early phase of AAD deregulation of the production of soluble and intracellular forms of adhesion molecule could result in lower levels of the intracellular form, such as ICAM-1, to compensate the release of circulating mediators, as illustrated in Fig. 2.…”
Section: Discussionsupporting
confidence: 93%
“…The systemic inflammation highlighted in AAD patients was also associated with an imbalance of pro-coagulant and vasoconstrictor factors including D-dimer, CFIII, s-Psel and EN-1, which are deregulated compared to controls, although we found no real differences between type A and B patients. Our findings with ICAM-1 agree with previous studies [28, 29], which reported that during the early phase of AAD deregulation of the production of soluble and intracellular forms of adhesion molecule could result in lower levels of the intracellular form, such as ICAM-1, to compensate the release of circulating mediators, as illustrated in Fig. 2.…”
Section: Discussionsupporting
confidence: 93%
“…Cytokines in particular are easily measured and are potential biomarkers of AKI. Several serum and urinary biomarkers have been recently investigated in AKI and characterised as more sensitive indicators of AKI than serum creatinine or urea nitrogen [46][47][48][49][50][51] . An ideal renal biomarker would be easily measured, inexpensive, sensitive to detection of subclinical injury and correlate prognosis with onset and severity of injury.…”
Section: Diagnosismentioning
confidence: 99%
“…More specifically, as far as open AAA repair and NGAL level changes are concerned, an increase in serum NGAL (75.21±55.83 vs. 46.37±21.60 ng/ml, p>0.05) and significantly elevated plasma NGAL levels at 2 h (91.54±76.54 vs. baseline, p<0.05), 12 h (100.78±44.92 vs. baseline, p<0.05), and 24 h (89.46±94.18 vs. baseline, p<0.05) after clamp release and reperfusion were found [33,34].…”
Section: Ngal and Aaa Natural Historymentioning
confidence: 94%
“…Additionally, AAA surgery triggers an inflammatory reaction and thus the increase of NGAL, which is known to be an acute-phase reactant produced by some immune cells [33]. NGAL has further been widely studied as an individual marker of acute kidney injury (AKI) induced by the AAA repair surgery, and it has been shown to increase due to decreased GFR with subsequent clearance impairment per se [34,35].…”
Section: Ngal and Aaa Natural Historymentioning
confidence: 99%
See 1 more Smart Citation